Dimensões metacognitivas no comportamento de busca de informação: estudo de usuário no arquivo público do estado do maranhão(APEM) - Barros, Dirlene Santos (2008)
Considering the user's study as the unique condition to comprehend the informational needs that lead the user to the search of the information to satisfy them, it is aimed to analyze, through the information search behavior mode'. of David Ellis, whether the metacognitive strategies of the information professional in Arquivo Publico do Estado do Maranhão (APEM) are similar or differ of those ones traced by the searchers in the behavior of the information search. It was intended to investigate the behavior characteristics in the information search of the researchers, identify their metacognitive strategies and check the validity of David Ellis' information search behavior for the user and the information professional in the archive. It was used the semi-structured interview to the APEM's professionals and the verbal protocol to the researchers. The choice of these instruments occurred because they permit personal reports and supply qualitative information. The semi-directive interview was applied with two professionals and the verbal protocol with twelve researchers, subdivided in two groups, one instructed and the other one non-instructed, where it was tried to identify the existence of their own or different metacognitive strategies in the categories of David Ellis' information search model. The results show there is a convergence in the information search behavior of these people in the APEM, with just a few differences. It was stid identified, the absence of a user study by the APEM in a systemic and centered way in its users.